Older adult preparedness for living with an endemic COVID-19 - TAN, Micah (Institutional Knowledge at Singapore Management University, 2022)
As Singapore holds steady against the current Omicron wave and begins to pave the next steps towards living with COVID-19, we hope that this report will provide our fellow colleagues and stakeholders with valuable insights into the perceptions and experiences of older adults in preparing to live with an endemic COVID-19. To this end, the current report examines several aspects of living with an endemic including whether older adults perceive themselves to be prepared, whether they are willing to adopt certain preventive behaviours, and the level of support they have for living with an endemic COVID-19. Specifically, we look at the following 7 aspects: Mental preparedness for living with an endemic COVID-19 Willingness to receive booster shots and factors influencing willingness Changes in behaviour in response to COVID-19 Use of self-medication against COVID-19 Support for Differentiated Safe-Management Measures Opinions on Vaccinated Travel Lanes Perceived infection and mortality rates from COVID-19